2004
DOI: 10.1002/glia.10341
|View full text |Cite
|
Sign up to set email alerts
|

Triethyltin‐induced stress responses and apoptotic cell death in cultured oligodendrocytes

Abstract: Triethyltin (TET)-induced neurotoxicity in the brain causes the formation of myelin edema and loss. Myelin deficits produced by early postnatal exposure to TET are permanent and cannot be repaired as the brain matures. The underlying causes have not been resolved. To investigate whether TET directly affects oligodendrocytes, the myelin-forming cells of the central nervous system, cultured rat brain oligodendrocytes were prepared and treated with TET. The data show that TET was cytotoxic for oligodendrocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Oligodendrocytes in culture constitutively express HSP32, HSP60 and HSC70. Exerting a variety of stress situations, including oxidative stress, heat shock, proteasomal stress and chemical stress induced by triethyltin chloride (Stahnke and Richter‐Landsberg, 2004), we did not observe the induction of HSP60 in cultured oligodendrocytes. HSP60 colocalizes with mitochondria (Fig.…”
Section: Stress Proteins In Oligodendrocytesmentioning
confidence: 63%
“…Oligodendrocytes in culture constitutively express HSP32, HSP60 and HSC70. Exerting a variety of stress situations, including oxidative stress, heat shock, proteasomal stress and chemical stress induced by triethyltin chloride (Stahnke and Richter‐Landsberg, 2004), we did not observe the induction of HSP60 in cultured oligodendrocytes. HSP60 colocalizes with mitochondria (Fig.…”
Section: Stress Proteins In Oligodendrocytesmentioning
confidence: 63%
“…HSP32/HO-1 may be considered as sensor of oxidative stress. The stress regulated kinases ERK1/2 have been shown to be activated under similar conditions that induce HO-1 transcription [ 23 ], and it has been suggested that the rapid and transient activation of ERK1/2 enhances the survival capabilities of cells, while a delayed response participates in the regulation of cell death [ 22 , 24 , 25 ]. The present data indicate that in neural cells the cytotoxic effects of TDA are associated with the induction of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…These progenitors (which are referred to as both oligodendrocyte-type-2 astrocyte [O-2A] progenitor cells ([47] and oligodendrocyte precursor cells, here abbreviated as O-2A/OPCs) are one of the most extensively studied of progenitor cell populations (reviewed in, e.g., [4852]. They also are among a small number of primary cell types that can be analyzed as purified populations, and at the clonal level, and for which there is both extensive information on the regulation of their development and also evidence of their importance as targets of multiple toxicants (including such chemically diverse substances as Pb [38,53], ethanol [e.g., [54–57]], and triethyltin [10,58]).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Fyn regulation of the Rho/ROCK signaling pathway could be of relevance in understanding toxicant-mediated alterations on such cytoskeletal functions as cell migration, neurite outgrowth, and development of dendritic morphology (e.g., [196198]). Our studies predict that any toxicant that makes cells and/or tissues more oxidized would activate Fyn, a list that includes substances as chemically diverse as MeHg (e.g., [16], Pb [69], and organotin compounds [1,2,5,10,11]), cadmium [12,13], arsenic [12,14], ethanol [15,16], and various herbicides (e.g., paraquat [17,18], pyrethroids [1921], and organophosphate and carbamate inhibitors of cholinesterase [2226]).…”
Section: Discussionmentioning
confidence: 99%